2016
DOI: 10.1149/2.0031608jss
|View full text |Cite
|
Sign up to set email alerts
|

Toward Practical Non-Contact Optical Strain Sensing Using Single-Walled Carbon Nanotubes

Abstract: Progress is reported in an emerging non-contact strain sensing technology based on optical properties of single-walled carbon nanotubes (SWCNTs). In this strain-sensing smart skin ("S 4 ") method, nanotubes are dilutely embedded in a thin polymer film applied to a substrate of interest. Subsequent strain in the substrate is transferred to the nanotubes, causing systematic spectral shifts in their characteristic short-wave infrared fluorescence peaks. A small diode laser excites a spot on the coated surface, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…One of the most basic solutions is to install contact-based vibration sensors in a dense manner throughout the structure, but it would be economically expensive and impractical to distribute sensors at all locations. Continuous and distributed sensing is possible with the ‘strain sensing smart skin’ that can be coated onto the surface of the structure to acquire strain data of high spatial resolution for estimating the dynamic strain directly [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Recently developed non-contact vision-based techniques like Digital Image Correlation (DIC) [ 11 , 12 , 13 , 14 , 15 ] are very suitable for full-field sensing.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most basic solutions is to install contact-based vibration sensors in a dense manner throughout the structure, but it would be economically expensive and impractical to distribute sensors at all locations. Continuous and distributed sensing is possible with the ‘strain sensing smart skin’ that can be coated onto the surface of the structure to acquire strain data of high spatial resolution for estimating the dynamic strain directly [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Recently developed non-contact vision-based techniques like Digital Image Correlation (DIC) [ 11 , 12 , 13 , 14 , 15 ] are very suitable for full-field sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotube emission is sensitive to local dielectric, hydrophobicity, redox potential, and surface potential, enabling optical sensing 29 . Nanotube optical sensors have been employed to detect analytes such as oligonucleotides 30 , cancer antigens 31 , proteins 32 , neurotransmitters 33 , reactive oxygen species 34 , lipids 35,36 , and to measure strain 37 in solid structures. We previously reported that photophysical properties and surface chemistry on SWCNTs can be modulated via encapsulation in helical polycarbodiimides 38 , polymers that enable unique control over nanotube surface chemistry, interactions with biomolecules and cells 39 , and facilitate subcellular targeting 40 .…”
Section: Introductionmentioning
confidence: 99%
“…When excited by visible light, the SWCNTs emit structured photoluminescence at short‐wave infrared wavelengths characteristic of their band gaps . Axial strains change the SWCNT band gaps in systematic ways, causing spectral shifts in the photoluminescence that can be used to deduce quantitative strain levels . Over the past few years, we have made progress toward developing a strain sensing technology based on this phenomenon .…”
Section: Introductionmentioning
confidence: 99%
“…Axial strains change the SWCNT band gaps in systematic ways, causing spectral shifts in the photoluminescence that can be used to deduce quantitative strain levels . Over the past few years, we have made progress toward developing a strain sensing technology based on this phenomenon . If load transfer from the surface of the structural element through the S 4 film to the SWCNTs is efficient, then each embedded nanotube will axially deform proportionally to the spatial projection of strain along that nanotube's axis.…”
Section: Introductionmentioning
confidence: 99%